Introduction to the special issue on education in Islamic civilization and the role of Islamic civilization on the formation of Malay identity - Mashitoh Yaacob, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2012)
This introductory paper first provides a brief overview of the current state-of-the-art of issues centered on Islamic civilization and Malay identity, followed by a synopsis of the articles included in this special issue. In addition, future perspectives on the expansion of discussions on the issues centered on Islamic civilization and Malay identity are outlined.